The nesting habits of Chalybion bengalense (Dahlbom) (Hymenoptera: Sphecidae). (2nd July 2020) - Pham, Phong Huy
ABSTRACT: The nesting habits of Chalybion bengalense are described. Copulation takes place at the nesting site. For nesting, the female uses old nests of Sceliphron and various eumenids, preexisting holes, and trap nests. The wasp cleans the nest cell and provisions it with paralyzed spider prey, 8–32 per S. madraspatanum (Fabricius) cell or 30–60 per trap nest cell. The female lays an egg on one of her prey, frequently the second or the third brought to the nest. Chalybion bengalense closes the nest cells with mud and on the cell cap adds an extra layer of lime, mud, cow dung, resinous material, or rotting plant. The total time from egg to emergence of the adult wasp is 27–34 days. The longevity of adults is 15–47 days for males and 21–49 days for females. Chalybion bengalense overwinters as prepupa from mid November to early April of the following year.